DEIKSIS DALAM NOVEL DARI HARI KE HARI KARYA MAHBUB DJUNAIDI - Yunita Eka Pratiwi; Rinjani Edelweiska; Dodi Firmansyah (Jurnal Bastra (Bahasa dan Sastra), 2025)
The purpose of this research is to describe the types of deixis in the novel from Dari Hari ke Hari by Mahbub Djunaidi. The research method used in this research is descriptive with qualitative research type. The technique used in analyzing deixis in the novel Dari Hari Ke Hari is using the technique of simak catat. The research conducted shows that in the novel Dari Hari Ke Hari by Mahbub Djunaidi there are six types of deixis, namely: 1) persona deixis is divided into three parts, namely, first persona deixis, second persona deixis, and third persona deixis. First person deixis consists of: I, me, we, and us. Second person deixis consists of: thou, you, your, and you guys. Third person deixis consists of: he, she, she, and they. 2) Place deixis consists of there, there, here. 3) Time deixis consists of yesterday, tomorrow, and the day after tomorrow. 4) discourse deixis refers to the use of terms such as "this" to indicate future discourse elements. Anaphora and katafora are included in discourse deixis. 5) Social deixis, is a reference made based on societal differences that have an impact on the role of the speaker and the listener. Certain usage shows social deixis. 6) pointer deixis is used to show the distance between the speaker and the designated object such as "this" and "that". The conclusion of this research is that there are six types of deixis, namely: person, place, time, discourse, social, and pointer deixis. The analysis shows that deixis has a significant role in the interaction between speakers and interlocutors.